Antiplatelet Therapy and Platelet Activity Testing for Neurointerventional Procedures - Keiko A Fukuda; Charles Beaman; Viktor Szeder (Stroke: Vascular and Interventional Neurology)
The management of antiplatelet medications in neurointerventional procedures remains a subject of considerable variability and debate. This review article explores the diverse clinical practices and the impact of different antiplatelet regimens and platelet activity testing on patient outcomes in neurointerventional treatments. While much of the evidence around antiplatelet therapies largely stems from randomized trials in cardiac and peripheral vascular diseases, their application in neurointerventional settings requires nuanced consideration. Various assays exist to assess individual platelet function, yet the optimal assay, thresholds, and agents remain uncertain due to interpatient variability in medication responsiveness. Expert consensus groups have attempted to standardize antiplatelet management, which is summarized for elective and emergent neurointerventional procedures. Clopidogrel, a commonly used antiplatelet, faces challenges such as genetic variability in metabolism and drug–drug interactions, impacting its effectiveness. Other agents, such as ticagrelor and prasugrel, offer alternatives with different mechanisms of action and potential advantages. Additionally, short‐acting intravenous P2Y12 inhibitors, such as cangrelor, and glycoprotein IIb/IIIa inhibitors provide options for acute bridging therapy in neurointerventional cases. Despite advancements, significant gaps persist in understanding the optimal antiplatelet management for neurovascular procedures. While platelet function testing is commonly used, its clinical utility and standardization remain an area of investigation. This review underscores the need for further multicenter studies to delineate best practices and optimize patient outcomes in neurointerventional settings.